Breastfeeding, maternal asthma and wheezing in the first year of life: a longitudinal birth cohort study. Issue 5 (2nd May 2017) - Azad, Meghan B.; Vehling, Lorena; Lu, Zihang; Dai, David; Subbarao, Padmaja; Becker, Allan B.; Mandhane, Piushkumar J.; Turvey, Stuart E.; Lefebvre, Diana L.; Sears, Malcolm R.
The impact of breastfeeding on respiratory health is uncertain, particularly when the mother has asthma. We examined the association of breastfeeding and wheezing in the first year of life. We studied 2773 infants from the Canadian Healthy Infant Longitudinal Development (CHILD) birth cohort. Caregivers reported on infant feeding and wheezing episodes at 3, 6 and 12 months. Breastfeeding was classified as exclusive, partial (supplemented with formula or complementary foods) or none. Overall, 21% of mothers had asthma, 46% breastfed for at least 12 months and 21% of infants experienced wheezing. Among mothers with asthma, breastfeeding was inversely associated with infant wheezing, independent of maternal smoking, education and other risk factors (adjusted rate ratio (aRR) 0.52; 95% CI 0.35–0.77 for ≥12 versus <6 months breastfeeding). Compared with no breastfeeding at 6 months, wheezing was reduced by 62% with exclusive breastfeeding (aRR 0.38; 95% CI 0.20–0.71) and by 37% with partial breastfeeding supplemented with complementary foods (aRR 0.63; 95% CI 0.43–0.93); however, breastfeeding was not significantly protective when supplemented with formula (aRR 0.89; 95% CI 0.61–1.30). Associations were not significant in the absence of maternal asthma (p-value for interaction <0.01). Breastfeeding appears to confer protection against wheezing in a dose-dependent manner among infants born to mothers with asthma. When mums with asthma #breastfeed longer, their babies are less likely to wheeze http://ow.ly/KWEk3089ZEn